Use, Perceptions, and Awareness of LibGuides among Undergraduate and Graduate Health Professions Students - Carey, John; Pathak, Ajatshatru; Johnson, Sarah C. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective – This study investigated usage, perceptions, and awareness of library research guides created using Springshare’s LibGuides among undergraduate and graduate health professions students.Methods – The researchers recruited 100 health professions students in April 2017 from Hunter College, a senior college within the City University of New York system. Participants were asked to complete a paper survey to ascertain their use, perceptions, and awareness of Springhare’s LibGuides.Results – Nearly two-thirds of study participants were not aware of library-created LibGuides and 68% had never used this tool. Compared to undergraduates, graduate students were more likely to be aware of LibGuides. The use of LibGuides was higher among graduate respondents (43%) than their undergraduate counterparts (30%). The study found low awareness and use of LibGuides among health professions students overall, regardless of age, gender, academic level, and health sciences concentration. Physical therapy students were more likely to use and be familiar with LibGuides than nursing, medical laboratory sciences, and speech-language pathology and audiology students. Participants reported using general subject guides more than course-specific guides, and the most commonly used page was the Databases guide. Of those participants who had used LibGuides, the vast majority (97%) said they found them useful in their studies.Conclusion – This study demonstrates low usage and awareness of LibGuides among health professions students at a large urban public college. Findings suggest a need for academic libraries serving such students to develop and implement strategies to promote awareness and increase usage of online research guides. The researchers recommend instructing with LibGuides during information literacy sessions and demonstrating their usefulness during reference consultations. Additional strategies include linking LibGuides to course sites through learning management systems such as Blackboard and collaborating with faculty members to better inform students about the guides.